Participation of young men and women in decision-making on sexual and reproductive health in Argentina: gender and socioeconomic asymmetries - Bolatti, Virginia Beatriz (2020)
Introduction: We analyse the participation of young women and men between 14 and 19 years old, in decision-making on two dimensions of sexual and reproductive health: the first sexual relationship and the use of contraceptive methods. Methodology: we use data from the first National Survey on Sexual and Reproductive Health (ESSyR) and we analyse differences by sex. We examined bivariate association measures by socio-economic status indices (High SES and Low SES). We construct the socioeconomic index using polychoric principal component analysis (ACPP). Finally, the differences by sex in decision making are visualized using Multiple Correspondence Analysis (MCA) for the different level of INSE. Results: The results suggest a differentiation by sex of the following dimensions: a) greater participation of men in decision-making regarding the first sexual relationship with respect to women, b) greater autonomy in men for decision-making about the contraceptive method to be used regularly and c) stability in the patterns of participation in decision-making between both SES, with some differences in the case of women. Conclusions: we suggest less satisfaction and autonomy of young women regarding the facts related to their sexual health than men.